An empirical comparison of hedging strategies with financial futures and options on futures - Ramin Cooper Maysami (Penerbit Universiti Kebangsaan Malaysia, 1995)
Hedgingfixed rate mortgage (FRM) portfolios with financial futures and options is suggested to substitutes for the adjustable rate mortgage as the hedging instrument. This study examines the comparative benefits of hedging the FRM through selling futures, buying puts, and the combined buy-putlsell-call strategies in lowering the standard deviation of returns of the unhedged portfolio over the period 1983 to 1991. The results show that covering the FRM through futures and options markets strategies are successful in lowering the variability of returns. The relative advantage of each strategy in terms of the mean-standard deviation pairs, however, depends on the direction of interest rate movements. Since the primary purpose offinancial institutions in hedging interest rate risk associated with their portfolio of fixed rate mortgages is to prevent values from falling as well as to reduce the variability of returns, the use of put options and finanCial futures as the hedging instrument is recomended.